Making wave : the story of variationist sociolinguistics - Tagliamonte, Sali (Hoboken, New Jersey : Wiley-Blackwell, 2016)
"Making Waves: The History of Variationist Sociolinguistics tells the human story of an academic field based on one-on-one interviews with 43 of the most famous scholars in Variationist Socioinguistics"--
Machine generated contents note: Preface viii 1 Where It Begins 1 2 Synchronicity and Sociolinguistics 25 3 A Crescendo of Research 53 4 Roots of Variationist Thinking 74 5 Sociolinguistics in the Street 88 6 Why Statistics Is in Your Head 107 7 Sociolinguistics From the Heart 121 8 Branching Out; Bursting at the Seams 131 9 Why Do You Like Variation? 158 10 Launching the Future 169 Afterword 185 Appendix A List of Interviews 186 Appendix B VSLX Family Tree 187 References 193 Index 000 .
Includes index.
Keywords: Language and languages -- Variation; LANGUAGE ARTS & DISCIPLINES / Linguistics / Sociolinguistics; Sociolinguistics -- Research; Speech acts (Linguistics)